Research on Low Liquid Holdup Two Phase Flow in Horizontal Pipe - Zhang, Xinhai; Li, Tong; Zhang, Yuxin; Liu, Yuanjie (International Journal of Electric Power and Energy Studies, 2024)
Low liquid content gas-liquid two-phase flow is widely present in wet natural gas pipelines and is one of the typical phenomena of gas-liquid two-phase flow. Liquid hydrocarbons and free water are consistently produced during the natural gas extraction and transportation processes due to factors such as pressure differentials and temperature fluctuations, leading to a low liquid-holdup pipe flow. Previous research has shown that this reduced liquid retention significantly increases pressure loss compared to single-phase gas flow. Accurately predicting pressure drop is crucial for the selection of pipeline size, pipe material, and pressurization equipment. At the same time, the liquid holdup rate is also an important parameter that determines the frequency of natural gas pipeline cleaning and the design of downstream equipment. Therefore, this article mainly focuses on the characteristics of gas-liquid two-phase flow with low liquid content during wet natural gas transportation. This article studies the gas-liquid two-phase flow patterns and different gas-liquid interface models in the literature. This article mainly compares and analyzes three low liquid content gas-liquid two-phase flow models in the literature.